Capacitação para agentes comunitários de saúde sobre a atenção à saúde do idoso - Villar, Veruska Ribeiro de Medeiros (2018)
Introduction: The Community Health Agent (ACS) has an important role in the health care of the elderly, because their attributions make possible the knowledge of the living conditions of the elderly in the family context and the community. Their work process is complex and requires permanent qualification, with the perspective of qualifying their attention to the health of the elderly. The objective of this study is to train and valorize this professional in order to contribute to the realization of health care for the integral of the elderly, as recommended by the PNSPI guidelines. Objectives: To identify in the scientific literature the perception of the ACS about the health care of the elderly in the primary care;Develop a Training Course on elderly health care for the ACS of a Health and Family Unit and Prepare a training course plan on elderly health care for the ACS.Methodology: This is a descriptive, qualitative research-action study in a Family Health Unit. Regarding ethical aspects, the project was submitted to the evaluation of the Ethics Committee of the Health Sciences Center (CCS) and approved under opinion No. 2,190 of July 27, 2017, and CAAE: 67103917.6.0000.5188. The participants of the research were ACS eigth from a Family Health Unit.To carry out the research, it followed the four phases of action research: phase 1: Training planning; phase 2: Acting to implement the planned improvement: this phase concerns the execution of the training of the ACS; Phase 3: Monitor action and Phase 4: Evaluation. Data analysis was performed in a descriptive way in all phases of the research. Results and Discussion: The result of this research was the production of two articles and one product, the first one being an integrative review article in the literature, which showed that care for the elderly in Brazil has gaps and flaws in the qualification of ACS as well as, point out that elderly people's health care and aging actions are not being implemented in Primary Care services. Based on this review, a training course on elderly health care for the ACSs was elaborated in a dialogical perspective, seeking to understand the gaps in the formation of ACS and allowing the reflection of its work process (Article 2) and the product was the qualification of the ACS resulting as an important moment of change of daily practice of ACS with the elderly. Conclusions: The training developed in this study contributed to the training of this professional, as he raised needs, developed permanent education actions, allowing reflections on his work process, offering new elements for the planning and execution of his actions and activities with the elderly, in a positive and integral perspective. From this research results the elaboration of a qualification for ACS on health care of the elderly.